Hospital pharmacists’ perspectives on diabetes treatment barriers and solutions: A qualitative study from Indonesia - Mika Tri Kumala Swandari; Zakky Cholisoh; Hidayah Karuniawati (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2025)
Background: Despite available treatment options, diabetes mellitus (DM) management faces significant barriers affecting patient outcomes. While most research focuses on patient factors, limited attention has been given to healthcare provider perspectives, particularly hospital pharmacists who are key stakeholders in diabetes care. Objective: This study explored treatment barriers and solutions from hospital pharmacists’ perspectives in Indonesia. Methods: This qualitative phenomenological study involved 18 hospital pharmacists at Cilacap Regional General Hospital, Central Java, Indonesia. Participants were selected through purposive sampling and had minimum one-year experience in diabetes patient care. Semi-structured interviews were conducted from January to February 2025, audio-recorded, transcribed verbatim in Bahasa Indonesia, and analyzed using thematic analysis. All interviews were conducted in Bahasa Indonesia and participant quotes were translated to English while preserving original meaning and cultural context. Results: Analysis of three predetermined barrier themes revealed: adverse drug reactions (ADRs) (particularly metformin-related gastrointestinal effects and insulin-associated hypoglycemia), medication non-adherence (influenced by feeling healed, treatment boredom, age-related denial, and therapy burden), and monthly follow-up challenges (geographic barriers, transportation difficulties, physical limitations, and insufficient family support). Pharmacists proposed comprehensive solutions including patient and family education, interprofessional collaboration, technology integration through WhatsApp support, and flexible monitoring approaches. Conclusion: Pharmacist-identified barriers operate as interconnected system components requiring multi-level interventions. Evidence-based solutions emphasizing education, collaboration, family engagement, and technological support can enhance diabetes management outcomes while respecting cultural contexts and resource constraints.